A GEOMETRICAL SYNTHESIS OF COMEZ TEXTILE MECHANISMS OF FINALLY REMOVED POSSIBILITIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
A synthesis of the COMEZ spatial knitting mechanism has been developed to convert rotational motion around a moving axle in a reciprocating motion. The synthesis has been done in extremely remote positions. For practical application of the synthesis, a vector-matrix approach is proposed in Math LAB Watt programming environment. With the specific metric parameters of the head mechanism, the function definition of the position is considered and a proposed eight-pointed mechanism replacing the spatial hump of the knitting head is proposed. To establish the authenticity of synthesis is an example.